IMPLEMENTASI PENGELOLAAN PROGRAM SHIMIN CENTER DI JEPANG DAN PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM ) DI INDONESIA - Dadang Yunus Lutfiansyach; Mustofa Kamil; Ace Suryadi; Elih Sudiapermana (IKIP Siliwangi, 2023)
This study examines the governance of Community Learning Centers (CLC) in 2 countries, namely the Shimin Center in Japan and PKBM in Indonesia. This study explores governance that includes program implementation in managerial aspects, namely the planning, implementation and evaluation functions carried out by Community Learning Centers in Indonesia and Japan. The theory underlying this research is the concept of lifelong education, the concept of community-based education and the concept of community education. This study uses a qualitative approach with a descriptive method. The data collection technique used in this research is through Focus Group Discussion (FGD), interview, observation, literature study and documentation study. The research subjects were 6 people, where 3 people from Shimin Center and 3 people from PKBM. The results of the study indicate that the implementation of the community learning center program both in Japan and in Indonesia in terms of aspects; a) program planning is always based on needs, formulation of objectives, program design, recruitment of facilitators and socialization and always refers to government policies; b) Implementation of programs developed by PKBM in Indonesia through a) Program Inputs (raw input, instrumental input, environmental input, process, output, other input and impact). As for the Shimin Center institution in Japan, it adheres to 3 main characteristics, namely the information center, a center for participation and self-actualization and is open to all ages and circles and is a place that guarantees freedom and equal rights, free services, has autonomy as a learning and cultural institution, has staff, is affordable (accessibility), adequate facilities and community participation; c) Evaluation of programs carried out by the Shimin Center in Japan and PKBM in Indonesia is carried out through evaluation of learning (formative and summative), evaluation of program services, personnel, and evaluation of educational unit institutions through unit quality assurance (accreditation). The evaluation carried out by the Japanese Government in managing the Shimin Center includes evaluation of learning carried out by volunteers/facilitators, in addition, evaluation is also carried out by asking for opinions from the community and community leaders.